Colorimetric determination of atmospheric nitrogen dioxide using preconcentration on C-18 cartridge. - Ugucione, C.; Neto, J. D.; Cardoso, A. A. (Soc Brasileira Quimica, 2002)
COLORIMETRIC DETERMINATION OF ATMOSPHERIC NITROGEN DIOXIDE USING PRECONCENTRATION ON C-18 CARTRIDGE, An alternative analytical method for nitrogen dioxide (NO,) in atmosphere was developed. The collection of NO, is performed by a Sep-Pack C-18 cartridge impregnated with 11 % (v/v) of triethanolaminc plus 3,6 % (v/v) of ethylene glycol plus 25 % (v/v) of acetone combined solution. When the impregnating is used, NO2 is collected with good repeatibility (CV 3,3 %). The NO, absorbed in the sampler was stripped from the sorbent with a methanol 5% (v/v) aqueous solution and was determined by colorimetry as nitrite by using the Griess-Saltzman reagent. The detection limit of 1,4 ppb for 60 min sampling at 0,5 L min(-1) flow rate was obtained. Preparation and conditioning procedures for TEA-C-18 cartridge, sampling flow rate, absorption capacity and interference of other species are discussed.
Keywords: nitrogen dioxide; triethanolamine; Griess Saltzman reagent